Iran against Islamic State (Daesh): Political Impacts on Pakistan - Muhammad Naveed ul Hasan Shah; Dr. AZ Hilali (Journal of Political Studies, 2019)
Islamic State of Iraq and Syria (ISIS), is said to be aTakfiri group, is mainly grabbed from Sunni areas of Syria and Iraq. Some other Muslim states also have their participation in IS by different means. Saudi Arabia and Turkey are in list of countries that were in foundation of Islamic State. In start they were in Syria and Iraq but now have their affiliations in many regions and countries. The Islamic State (IS) is a big threat to Middle East and world. It is argued that many European and Pakistani nationals are also part of Islamic State. Pakistani Talban's have affiliations with Baghdadi, and it is trouble for Pakistan in future. The proxy war between Iran and Saudi Arabia is problem for Pakistan and Muslim world because both are supporting their allies and muscles. 300 Saudis have killed in Syria in February 2014, which also is the highest number of loss of life among Saudi nationals. In March 2014, a Saudi official said that 1,200 Saudi citizens have traveled to fight the Assad regime. US has also its role in IS and following duel policy against IS in Iraq and Syria. Russia is strong supporter of Asad and has launched a military and air strike against anti Asad forces.The main purpose of this research is to analyze process of evolution of Islamic State (IS) and its impacts both political and strategic not only on the Middle East but on Pakistan also.